The Secret: The Power - Byrne, Rhonda (London Simon & Schuster, 2010)
Rhonda believes that everyone is meant to have an amazing life. And in The Power, she shows how perfect health, incredible relationships, a career you love, a life filled with happiness, and the money you need to be, do, and have everything you want, all come from The Power. The Power is the handbook to the greatest power in the universe - The Power to have everything you want.
The Secret revealed the law of attraction. The greatest power in the universe is the power to have anything you want. One thing can change your relationships, money, health, happiness, career, and life. The life you want comes from the Power.
Keywords: Control (Psychology) -- Self-actualization (Psychology) -- Success--Psychological aspects -- Happiness -- Self-realization -- Success -- Immortalism -- Self-help techniques